Host-parasite interactions between Plasmodium species and New Zealand birds : prevalence, parasite load and pathology : a thesis presented in partial fulfilment of the requirements for the degree of Master of Veterinary Science in Wildlife Health at Massey University, Palmerston North, New Zealand - Sijbranda, Danielle Charlotte (Massey University, 2015)
Avian malaria, caused by Plasmodium spp., is an emerging disease in New Zealand and has been reported as a cause of morbidity and mortality in New Zealand bird populations. This research was initiated after P. (Haemamoeba) relictum lineage GRW4, a suspected highly pathogenic lineage of Plasmodium spp. was detected in a North Island robin of the Waimarino Forest in 2011. Using nested PCR (nPCR), the prevalence of Plasmodium lineages in the Waimarino Forest was evaluated by testing 222 birds of 14 bird species. Plasmodium sp. lineage LINN1, P. (Huffia) elongatum lineage GRW06 and P. (Novyella) sp. lineage SYATO5 were detected; Plasmodium relictum lineage GRW4 was not found. A real-time PCR (qPCR) protocol to quantify the level of parasitaemia of Plasmodium spp. in different bird species was trialled. The qPCR had a sensitivity and specificity of 96.7% and 98% respectively when compared to nPCR, and proved more sensitive in detecting low parasitaemias compared to the nPCR. The mean parasite load was significantly higher in introduced bird species compared to native and endemic species. The data suggests that introduced bird species such as blackbirds have a higher tolerance for Plasmodium spp. infections than endemic and native species. The high prevalence of infection and high parasite load in introduced passerines confirmed that they are important reservoirs for avian malaria in the New Zealand. A clinical case of avian malaria in a captive wildlife setting was described for a little penguin (Eudyptula minor) at Wellington Zoo. Nested PCR results and DNA sequencing confirmed infection of the deceased penguin with Plasmodium (Huffia) elongatum GRW06. A retrospective analysis of little penguin cases in the Massey University post mortem database, combined with nested PCR for Plasmodium spp. on stored liver tissue samples and DNA sequencing, revealed three additional mortality cases due to P. elongatum lineage GRW06, P. relictum lineage SGS1 and P. sp. lineage LINN1 in one captive and two wild little penguins. Our results suggest that avian malaria causes sporadic mortality in New Zealand’s little penguins, but there is no evidence of mass mortality events due to avian malaria in this species.
Keywords: Avian malaria; Birds; Parasites; Plasmodium; New Zealand